Corpus-based vocabulary lists for language learners for nine languages - Kilgarriff, Adam; Charalabopoulou, Frieda; Gavrilidou, Maria; Johannessen, Janne Bondi; Khalil, Saussan; Johansson Kokkinakis, Sofie; Lew, Robert; Sharoff, Serge; Vadlapudi, Ravikiran; Volodina, Elena (My University, 2014)
We present the KELLY project and its work on developing monolingual and bilingual word lists for language learning, using corpus methods, for nine languages and thirty-six language pairs. We describe the method and discuss the many challenges encountered. We have loaded the data into an online database to make it accessible for anyone to explore and we present our own first explorations of it. The focus of the paper is thus twofold, covering pedagogical and methodological aspects of the lists’ construction, and linguistic aspects of the by-product of the project, the KELLY database.
Keywords: Corpora; Language learning; Vocabulary; Frequency; Frequency lists